FAKTOR-FAKTOR YANG MEMPENGARUHI INFLASI DI INDONESIA - Chairannisa Arjunita (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2016)
This study aims to  analyze the effect of interest rate, money supply,exchange rate and inflation targeting framework policy on inflation in Indonesia.The type of this research are descriptive and associative using time series data fromthe first quarter of 1997 until the fourth quarter of 2015 with documentation datacollected technique. Data were analyzed with multiple linear regression model, theprerequisite test (multicolinearity, autocorrelation and heteroscedasticity), t test, andF test. The result shows that (1) Interest Rates has positive and significant effect oninflation in Indonesia. (2) Money Supply has positive and not significant effect oninflation in Indonesia. (3) Exchange rate has negative and not significant effect oninflation in Indonesia.  (4) Inflation Targeting Framewrok Policy has positive andsignificant effect on inflation in Indonesia.